Saha and his formula - Venkataraman, G. (Hyderabad, Universities Press (India) Limited, 1995)
A great leap forward in unravelling the mysteries of the Sun occurred way back in 1920 when Meghnad Saha made an important discovery that paved the way for a systematic study of stellar atmospheres in general. This book is about that great discovery and the man who made it.
Index 191-194p.
Keywords: Contributions; Astronomy